2020
DOI: 10.1097/pep.0000000000000736
|View full text |Cite
|
Sign up to set email alerts
|

Intraobserver Reliability and Construct Validity of the Squat Test in Children With Cerebral Palsy

Abstract: Purpose: This study evaluated intraobserver reliability and construct validity of the squat test to assess lower extremity strength in children with cerebral palsy (CP) and spastic diplegia. Methods: Children with CP performed 2 trials of the squat test and calculated the intraclass correlation coefficient to evaluate intraobserver reliability. Correlations between outcomes of hand-held dynamometry (HHD) of knee extensor strength and an 8-repetition max… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The DST is used in other clinical settings and has been previously shown to have both validity and reliability in assessing strength in the lower limb for patients with cerebral palsy(CP) (14). The reliability of the DST from Ekens et al, (2020) (14) study cannot be generalised to patients with FAIS, insofar that the subjects were children with CP who were asked to perform two trials of 20 squats on the same day correlating squat pattern with leg strength. Furthermore, the reliability of the DST was judged on well executed squat rather than pain or restriction.…”
Section: Discussionmentioning
confidence: 99%
“…The DST is used in other clinical settings and has been previously shown to have both validity and reliability in assessing strength in the lower limb for patients with cerebral palsy(CP) (14). The reliability of the DST from Ekens et al, (2020) (14) study cannot be generalised to patients with FAIS, insofar that the subjects were children with CP who were asked to perform two trials of 20 squats on the same day correlating squat pattern with leg strength. Furthermore, the reliability of the DST was judged on well executed squat rather than pain or restriction.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported promising results for HHD measurement of knee extension strength in children with CP with GMFCS levels I-II [29]. The start position was an upright sitting position with the hip and knee joints at 90° and the upper limbs crossed in front of the chest [30]. The knee extension strength-to-body weight ratio (kgf/kg) of the dominant leg was calculated.…”
Section: Knee Extension Strengthmentioning
confidence: 99%
“…A comprehensive assessment of sensory abnormalities in CP children will eventually result in an appropriate course of treatment, which will further enhance motor function as well (3) . Various reliability studies were also conducted earlier in the search of a reliable outcome measure for CP children but most of them solely focused on one domain like the Upper Extremity function (4) , assessment of balance-related tests (5) , motor power (6) , gross motor function assessment, and gait assessment (7) . However, other than SOMH, no scale has been developed yet for the Indian CPs to evaluate sensory impairments (8) .…”
Section: Introductionmentioning
confidence: 99%